2009
DOI: 10.1002/bit.22214
|View full text |Cite
|
Sign up to set email alerts
|

3D culture of osteoblast‐like cells by unidirectional or oscillatory flow for bone tissue engineering

Abstract: A medium perfusion system is expected to be beneficial for three-dimensional (3D) culture of engineered bone, not only by chemotransport enhancement but also by mechanical stimulation. In this study, perfusion systems with either unidirectional or oscillatory medium flow were developed, and the effects of the different flow profiles on 3D culturing of engineered bone were studied. Mouse osteoblast-like MC 3T3-E1 cells were 3D-cultured with porous ceramic scaffolds in vitro for 6 days under static and hydrodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 42 publications
2
61
0
Order By: Relevance
“…Images obtained by standard experimental techniques are mainly limited to surface restricted TE construct characterization as they are line-of-sight techniques and only provide limited depth information. 50,52 Not taking into account the latter limitation may result in the misinterpretation of statically cultured TE constructs as being full of ECM, while in reality only an outer layer of ECM exists, as confirmed by CE-nano-CT (Fig. 4).…”
Section: Papantoniou Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Images obtained by standard experimental techniques are mainly limited to surface restricted TE construct characterization as they are line-of-sight techniques and only provide limited depth information. 50,52 Not taking into account the latter limitation may result in the misinterpretation of statically cultured TE constructs as being full of ECM, while in reality only an outer layer of ECM exists, as confirmed by CE-nano-CT (Fig. 4).…”
Section: Papantoniou Et Almentioning
confidence: 98%
“…Fluid flow is known to enhance matrix synthesis within TE constructs during perfusion culture. 19,40,50 Furthermore, differences in fibrillar collagen organization of the ECM, which are flow dependent, 51 could also explain the ECM differences that were observed by PTA staining as the ECM morphology could influence the binding mechanism of PTA to the ECM proteins. In Figure 5, it may also be observed that the difference in collagen content, as determined by Picrosirius Red staining, for the different flow rates is less pronounced than the one observed with the PTA staining.…”
Section: Papantoniou Et Almentioning
confidence: 99%
“…Images of scaffolds observed at 10x objective of a fluorescence stereomicroscope are shown afcording to the regions indicated by the broad views on the left. (Du et al, 2009) In contrast, the scaffolds cultured by the oscillatory flow had a relatively uniform distribution of livnig cells throughout the scaffolds. The inhomogeneous living cells distribution of the unidirectional perfusion culture was further verified by higher magnificaion, as shown in Figure 14.…”
Section: Oscillatory Perfusion Culture Of Cap-based Tissue Engineerinmentioning
confidence: 88%
“…A: The unidirectional perfusion system; (b) the oscillatory perfusion system. (Du et al, 2009) A gas-permeable bag was set in the circuit loop as a gas exchanger. The unifirectional media flow was driven bya syringe ponp.…”
Section: Oscillatory Perfusion Culture Of Cap-based Tissue Engineerinmentioning
confidence: 99%
“…Although static seeding is the most commonly used method, low seeding efficiencies and non-uniform cell distributions are often G Bouet et al In vitro 3D bone culture model reported (Alvarez-Barreto and Sikavitsas, 2007;Burg et al, 2000;Holy et al, 2000). Therefore, based on the literature (Du et al, 2009;Godbey et al, 2004;Janssen et al, 2006a), a dynamic seeding technique was used in this study. Combined with the architecture of the scaffolds, this resulted in a uniform cell colonisation and distribution within the scaffold interior.…”
Section: G Bouet Et Almentioning
confidence: 99%